Impact of a school-based intervention on nutritional education and physical activity in primary public schools in Chile (KIND) programme study protocol: cluster randomised controlled trial. (December 2016) - Bustos, Nelly; Olivares, Sonia; Leyton, Bárbara; Cano, Marcelo; Albala, Cecilia
Abstract Background Chile has suffered a fast increase in childhood obesity in the last 10 years. As a result, several school programmes have been implemented, however the effectiveness of these needs to be evaluated to identify and prioritize strategies to curve this trend. Methods Cluster randomized controlled trial. Twelve primary public schools chosen at random over three regions of the country will take part in this study. The sample size consisted of a total of 1, 655 children. For each region one school will be selected for each of the three nutritional intervention modes and one school will be selected as the control group. The intervention modes consist of the following:Healthy Kiosk and nutritional education (KSEAN); Optimized physical activity (AFSO); Healthy Kiosk and nutritional education (KSEAN) + optimized physical activity (AFSO); Control group. The effectiveness of each intervention will be evaluated by determining the nutritional condition of each child by measuring percentage of body fat, BMI and the z-score of the BMI. This study will also identify the eating behaviours, nutritional knowledge and fitness of each child, along with the effective time of moderate activity during physical education classes. Discussion A protocol to evaluate the effectiveness of a school based intervention to control and/or reduce the rates of childhood obesity for children between 6 and 10 years of age was developed. The protocol was developed in line with the Declaration of Helsinski, the Nüremberg Code and the University of Chile Guidelines for ethical committees, and was approved by the INTA, Universidad de Chile ethical committee on Wednesday 12 March 2014. There is consensus among researchers and health and education personnel that schools are a favourable environment for actions to prevent and/or control childhood obesity. However a lack of evidence on the effectiveness of interventions to date has led some to question the wisdom of allocating resources to programmes. This is the first study of this kind in Chile and could be an important first step to provide guidance to political authorities in relation to which food and nutrition strategies to prioritize to curve this alarming trend. Trial registration ISRCTN32136790, registered retrospectively on 05 September 2014.